Elephants and ivory in the Congo since the ban: the lull before the storm? - J. Fay; Marcellin Agnagna (Pachyderm)
On average, the raw ivory from between 2,011 and 3,788 elephants was exported with documentation from the Congo every year from 1979 to 1988. The actual figure must have been undoubtedly much more than the official one. It is evident that the Congo participated actively in the ivory trade resulting in a dramatic decrease in populations throughout the ranges in the 1980's. The 1989 ban on ivory trade and subsequent collapse of the market has led to a significant decrease in both poaching and ivory trade. The Congo has made significant advances in the domain of conservation resulting in positive results in elephant protection in some areas.